2007
DOI: 10.1038/sj.bjp.0707225
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits nitric oxide production by microvascular endothelial cells in vivo and in vitro

Abstract: Background and purpose: We have previously shown that melatonin inhibits bradykinin-induced NO production by endothelial cells in vitro. The purpose of this investigation was to extend this observation to an in vivo condition and to explore the mechanism of action of melatonin. Experimental approach: RT-PCR assays were performed with rat cultured endothelial cells. The putative effect of melatonin upon arteriolar tone was investigated by intravital microscopy while NO production by endothelial cells in vitro w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 63 publications
5
40
0
14
Order By: Relevance
“…Our data are supported by the observation that melatonin inhibits expression of nitric oxide synthase in different settings (24,25). Furthermore, melatonin was recently reported to attenuate nitric oxide production by endothelial cells in vivo (26). Therefore, our results allow the conclusion that melatonin improves hepatic perfusion by presinusoidal adaptations.…”
Section: Discussionsupporting
confidence: 89%
“…Our data are supported by the observation that melatonin inhibits expression of nitric oxide synthase in different settings (24,25). Furthermore, melatonin was recently reported to attenuate nitric oxide production by endothelial cells in vivo (26). Therefore, our results allow the conclusion that melatonin improves hepatic perfusion by presinusoidal adaptations.…”
Section: Discussionsupporting
confidence: 89%
“…One potential site of action for melatonin could be endothelial NO synthase (eNOS). Indeed, melatonin inhibits NO production in rat microvascular endothelial cells (Silva et al, 2007), although this effect is not observed in larger arteries of the rat (Monroe and Watts, 1998). Although an effect of melatonin on eNOS in porcine coronary arteries cannot be ruled out, the observation that melatonin also inhibits relaxation induced by SNP, which is independent of eNOS (Kowaluk et al, 1992), suggests a site of action for melatonin other than, or in addition to, eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…a,b-MeATP, presumably acting via P2X 1 or P2X 3 receptors, caused production of NO by microvascular endothelial cells from rat cremaster muscle; unlike the actions of 2-methylthio ATP (2-MeSATP) at coexpressed endothelial P2Y 1 receptors, NO production by a,b-meATP was unaffected by melatonin, indicating distinct sites of action (Silva et al, 2007). It was reported that P2X 1 receptors are expressed in the endothelium of rat mesenteric arteries and that their activation leads to vasodilation largely via EDHF (Harrington and Mitchell, 2004).…”
Section: Purinergic Signaling and Blood Vesselsmentioning
confidence: 99%